Restorative Justice Approach in Order to Resolve Physical Violence Committed by Husbands Against Wives In Maluku Regional Police - Sopacua, Margie Gladies; Iqbal Taufik; Denni Latumaerissa; Leonie Lakollo (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2024)
This paper examines the effectiveness of resolving physical violence against wives at the investigation stage carried out by investigators from the Women and Children Protection Unit (UPPA) of the Maluku Regional Police (Polda) through a restorative justice approach. This research is a sociological juridical (empirical) research. Efforts to resolve physical violence against wives at the investigation stage are carried out by UPPA investigators of the Maluku Regional Police (Polda) through restorative justce in the form of; (1) Involve all parties interested in the problem of crime (violence) to participate in solving collectively or together; (2) The perpetrator does not refuse and is willing to commit and is voluntarily responsible for compensating for the violence committed; and (3) Provide opportunities to the perpetrator in terms of reaching a resolution to the violence committed against his wife. The resolution of physical violence against wives at the investigation stage carried out by investigators from the Women and Children Protection Unit of the Maluku Regional Police based on the resolution efforts described above through a restorative justice approach has been effective, this is because the victim does not want to continue the case to the court stage which will lead to divorce.